Nanofabrication of high Q, transferable diamond resonators. Issue 19 (4th May 2021) - Regan, Blake; Trycz, Aleksandra; Fröch, Johannes E.; Schaeper, Otto Cranwell; Kim, Sejeong; Aharonovich, Igor
Abstract : Schematic illustration of a 1D diamond nanobeam cavity. Abstract : Advancement of diamond based photonic circuitry requires robust fabrication protocols of key components – including diamond resonators and cavities. Here, we present 1D (nanobeam) photonic crystal cavities generated from single crystal diamond membranes utilising a metallic tungsten layer as a restraining, conductive and removable hard mask. The use of tungsten instead of a more conventional silicon oxide layer enables good repeatability and reliability of the fabrication procedures. The process yields high quality diamond cavities with quality factors ( Q -factors) approaching 1 × 10 4 . Finally, we show that the cavities can be picked up and transferred onto a trenched substrate to realise fully suspended diamond cavities. Our fabrication process demonstrates the capability of diamond membranes as modular components for broader diamond based quantum photonic circuitry.